2017
DOI: 10.1097/gox.0000000000001248
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Aesthetic Thorax Reconstruction after Desmoid Tumor Resection

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Desmoid tumors can originate anywhere within the body but are most common in the trunk and extremities. 13 Desmoid tumors are known to arise from muscular fascia or aponeurosis 1,14 and are also believed to arise within the pectoralis major muscle fascia or Cooper ligament. 14 Jewett, in 1979, suggested that when desmoid tumors are associated with breast implants, they could arise from the fibrous capsule that forms around the implant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desmoid tumors can originate anywhere within the body but are most common in the trunk and extremities. 13 Desmoid tumors are known to arise from muscular fascia or aponeurosis 1,14 and are also believed to arise within the pectoralis major muscle fascia or Cooper ligament. 14 Jewett, in 1979, suggested that when desmoid tumors are associated with breast implants, they could arise from the fibrous capsule that forms around the implant.…”
Section: Discussionmentioning
confidence: 99%
“…In three of the case reports reviewed, [16][17][18] a second desmoid tumor developed at a surgical site remote from the implant, and Case 2 from our series developed a secondary and fibroproliferative disorders of the mesenchymal tissue has been hypothesized. 13 The Wnt/beta-catenin signaling pathway plays an important role in tissue repair, and mutations within the CTNNB1 gene encoding beta-catenin have been found in 85% of sporadic desmoid tumors 13,19 Remarkably, the rate of CTNNB1 mutations is lower in breast desmoid tumors, being around 77%. 20 Moreover, the APC protein suppresses CTNNB1 transcription, explaining the association between FAP-where the APC gene is mutated-and desmoid tumors.…”
Section: Discussionmentioning
confidence: 99%